The Protection of Non-Combatants During Armed Conflict and Safeguarding the Rights of Victims in Post-Conflict Society Essays in Honour of the Life and Work of Joakim Dungel - Ambach, Philipp (BRILL, 2015)
This collection of essays-written by friends and colleagues of Joakim Dungel-focuses on the protection of the innocent during and after war. It is a tribute to Joakim's life and work. Joakim made a significant contribution to international justice and the rule of law, through his service to the United Nations International Criminal Tribunals for the former Yugoslavia and Rwanda, the Special Court for Sierra Leone, the Temporary International Presence in Hebron, and the United Nations Assistance Mission in Afghanistan. He was also a prolific author and published scholarly works on a wide range of issues, including command responsibility, national security interests, the right to humanitarian assistance during internal armed conflicts, and crimes against humanity. This book continues Joakim's work with in-depth analyses of a variety of issues arising under modern conflict, such as the application of international humanitarian law and international human rights law to aerial drone attacks, targeted sanctions, and reparations to victims. Joakim understood these complex and interlinked issues and dedicated his professional life to engaging with them. Through his work and his scholarship, he demonstrated the crucial importance of adopting victim-centred approaches to dealing with the consequences of armed conflict and to its prevention. This was also why he chose to work for the United Nations as a human rights officer in Afghanistan. This book attempts to honour and affirm Joakim's choice